Pengaruh Komitmen Organisasi Dan Kompetensi Auditor Terhadap Kinerja Auditor Pada Kantor Inspektorat Daerah Provinsi Lampung (Study Kasus pada Kantor Inspektorat Daerah Provinsi Lampung) - Herry Goenawan Sudarsa; Anniza Ratu Mahlinda; Riswan RISWAN (Universitas Bandar Lampung (UBL), 2012)
The main objective of this study was to determine the effect of organizational commitment and competence of the auditors on the performance of auditors Regional Inspectorate Office of Lampung Province. Based on the analysis results, indicate that organizational commitment and competence of auditors have an influence on the performance of auditors. Based on the analysis results, the authors recommend the need to increase the love of organizations comply with regulations such as leadership, doing work optimally for the organization, and willing to sacrifice for the sake of the organization, even in a very urgent situation auditor must always exist for increased auditor competence organisasi.Perlu especially in works. Experience and knowledge of the auditor shall be increased by way of response to the environment of auditors and senior auditors others outside the organization. And seminars related to the auditors work in order to increase knowledge and experience for the auditor. Because competent auditor is needed in the most important is organisasi.Yang should improve the performance of auditors in the audit teams work in the form of value the opinion of a teammate, not to be selfish, to be responsible, honest, obedient to the organizations rules, and loyal to the organization . Head of the Office of Lampung Province Inspectorate through Kasub. Personnel should be more assertive attention to the performance of the auditor and the auditor should follow the trainings and seminars to increase knowledge and experience related to the auditors work.